2016
DOI: 10.1021/acs.jpcc.5b10856
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Photocatalytic Activity of BiVO4 for Oxygen Evolution by Ce Doping: Ce3+ Ions as Hole Traps

Abstract: To enhance the photocatalytic activity of monoclinic BiVO4 for O2 evolution from water, Ce-doped BiVO4 was prepared using the one-pot facile solvothermal method and characterized via XRD, Raman, XPS, and electrochemical impedance spectroscopy (EIS). The XPS spectra confirm that Ce component is Ce3+ ions instead of Ce4+ ions. From the structural characterization and the calculations of formation energies it has been stated that the doping of Ce3+ ions takes place at Bi3+ sites without changing the host structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 38 publications
4
89
0
3
Order By: Relevance
“…The absence of sulphur peak above 164 eV further indicated for the absence of elemental sulphur or the polymeric gold sulphide that usually forms in case of thiol stabilized Au NPs. The presence of V 2p 3/2 and V 2p 1/2 at 516.6 eV and 524.3 eV with O1s signal at 532.0 eV was in accordance with our proposed structure of AuVNF (Figure S3c) . The BE value corresponds to the +5 oxidation of vanadium which was in accordance with CV analysis and the presence O 1s peak at 532 eV suggested for the coordination of carboxylic unit with vanadium center (Figure S3c) .…”
Section: Resultssupporting
confidence: 87%
“…The absence of sulphur peak above 164 eV further indicated for the absence of elemental sulphur or the polymeric gold sulphide that usually forms in case of thiol stabilized Au NPs. The presence of V 2p 3/2 and V 2p 1/2 at 516.6 eV and 524.3 eV with O1s signal at 532.0 eV was in accordance with our proposed structure of AuVNF (Figure S3c) . The BE value corresponds to the +5 oxidation of vanadium which was in accordance with CV analysis and the presence O 1s peak at 532 eV suggested for the coordination of carboxylic unit with vanadium center (Figure S3c) .…”
Section: Resultssupporting
confidence: 87%
“…[20,21] To optimize catalytic performance, doping of the metal oxide catalysts with additional metal atoms has been put forward as a means of controlling the physical and electronic structure of the composite. [27][28][29] Different hypotheses have been put forward to explain this effect: Shao et al suggested that the Fe doping leads to an improved electronic structure of the catalytically active surface site, [26] while Alonso-Mori et al suggested that the Fe doping improves the electrical conductivity of the catalysts. [25,26] This was exemplified by the introduction of iron ions into various metal oxide host lattices, leading to significantly improved OER catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4B−E are the high‐resolution spectra of Bi4 f, V2p, O1s, and Pd3d, respectively. In the Bi4 f XPS spectrum (Figure 4B), splitting peaks centered at 159.04 and 163.29 eV, corresponding to the characteristic spin‐orbit split of Bi4f 5/2 and Bi 4f 7/2 signals . In Figure 4 C, the V2p orbital exhibited splitting peaks at 516.80 and 522.65 eV, corresponding to the characteristic spin‐orbit split of V2p 1/2 and V2p 3/2 signals .…”
Section: Resultsmentioning
confidence: 96%
“…These outcomes indicated that chemical states of Bi and V were 3+ and 5+, respectively . The O 1s spectra (Figure 4 C) of 0.5%‐Pd‐BVO samples at a binding energy (BE) of 529.7 eV could be deconvoluted into three pairs of individual components referring to the surface lattice oxygen (529.69 eV), the surface adsorbed oxygen species (530.62 eV), and water (531.96 eV) . The surface lattice oxygen was indexed to the O–Bi and V–O bonds in BiVO 4 crystal lattice or Pd–O in PdO crystal lattice.…”
Section: Resultsmentioning
confidence: 99%